(untitled) (Research, Society and Development, 2020)
The objective was to characterize the structure of the shrub-tree community in Seasonal Semideciduous Forests (FES) seeking to investigate the richness and the similarity of species between the areas. Three environments were evaluated in a Permanent Preservation Area: FES Submontana; Alluvial FES and Secondary Vegetation Area (AVS). Through the contiguous plot method, individuals with CAP equal to or greater than 10 cm / 1.30 m from the soil were identified. For data analysis, NMDS ordering based on the Bray-Curtis dissimilarity matrix, cluster analysis (UPGMA), Venn diagram, alpha diversity and phytosociological parameters (Dr, DoR, FR, IVI, IVC). A total of 2,780 individuals were registered. The sampled areas resulted in three environments significantly different in terms of community structure (Pillai = 1.25; df = 4 and 294; p <0.001), where FESS showed the highest index of diversity and species richness. The analysis (UPGMA) revealed a group between FESA and AVS with a coefficient of 0.65. The greater specific diversity and richness of species in FESS indicate high floristic heterogeneity. The lower diversity in FESA and AVS respectively, may reflect the edaphoclimatic characteristics of the place. The composition of different species is justified due to the natural regeneration process having different successional trajectories, which can be influenced by multiple factors. The importance of preserving these environments is emphasized for the maintenance of the region’s floristic wealth, as they safeguard valuable floristic information, and may represent a model for the revegetation of areas under similar conditions, as well as for supporting management and recovery proposals degraded areas.